The tablet has landed. - Ochs, Susie (Mac life)
After years of speculation, Apple's tablet--the iPad--is almost here. We've spent hours using several iPads, and they're the closest thing to a notebook that Apple will ever make. Our no-holds-barred analysis will help you understand that iPads are good for--and whether you should buy one.